Disaster Preparedness School Program As An Effort To Increase The Capacity Of Disaster-Vulnerable Groups In Mataraman Sub-District - Fauzie Rahman; Nur Laily; Anggun Wulandari; Zuhrufa Wanna Yolanda (Lambung Mangkurat University, 2024)
Flood disasters tend to have a greater impact on vulnerable communities, including school children, who are at the highest risk. Therefore, elementary schools are the primary target of the community service activities carried out. Disaster risk reduction for vulnerable groups is an effort to manage disaster risk for vulnerable groups by increasing their resilience.The aim of this activity is to increase students’ knowledge, understanding, and capacity regarding disasters. The activities were carried out face to face using lectures, videos, powerpoint presentations, and banners. Community service activities in the form of a disaster preparedness school program has been successfully implemented, as evidenced by an increase in student knowledge among 21 students (65.6%). The results of statistical tests show a significance value of 0.000 < 0.05, meaning that there is a significant difference between the average pre-test and post-test scores. This suggests that there is an effect of the health education carried out on increasing students' knowledge regarding how to prevent floods and actions that must be taken during floods at SDN Mataraman 3, Banjar. Therefore, it can be concluded that the community service activities can provide school students with an understanding of how to prevent floods and actions that must be taken during floods. It is hoped that by increasing their understanding, students can become educational agents for their families, friends and the surrounding community, thereby they can increase the community's capacity to deal with floods.